A Gamified Mobile Telerehabilitation Framework for Improving Exercise Adherence in Older Adults - Triandini, Evi; Sangsawang, Thosporn; Kuswanto, Djoko (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The efficacy of long-term rehabilitation programs is diminished by older persons' poor adherence to recommended rehabilitation exercises. Even though telerehabilitation has made rehabilitation services more accessible, many current systems still offer disjointed support, frequently handling clinical monitoring, exercise delivery, and motivation independently rather than in a single digital workflow. In order to improve exercise adherence, this study suggests a gamified mobile telerehabilitation framework for older persons that incorporates clinician-supervised monitoring, gamification, and rehabilitation management. The study uses the Design Science Research (DSR) methodology, emphasizing framework design, objective formulation, and problem identification. A centralized application server connects the patient, clinician, and system support modules that make up the suggested structure. This study's novelty innovation is the comprehensive fusion of gamification, adaptive rehabilitation, and ongoing clinical input into a unified telerehabilitation architecture created especially for senior citizens. A structured conceptual framework that links clinician decision-making, patient exercise activities, and motivational support systems into a single coordinated system is the main contribution. The problem formulation, design objectives, system architecture, use-case flow, and framework design serve as the basis for further prototype development, and the outcomes are currently conceptual rather than empirical. Consequently, this study does not report any empirical effectiveness outcomes. In order to assess the framework's potential to enhance exercise adherence, user engagement, and remote rehabilitation monitoring, the next phases will involve UI/UX implementation, prototype development, demonstration, and evaluation.